profile
Опубликовано - 1 месяц назад | По предмету Математика | автор Аноним

Докажите равенство: б) (a-1)^2+2(a-1)+1=a^2; в) (x+1)^2-4(x+1)+4=(x-1)^2; г) (x-y)^2-2(x-y)(x-y)+(x-y)^2=4y^2.

  1. Ответ
    Ответ дан Горшков Мстислав
    Докажем тождества:
    б) ( a - 1 ) ^ 2 + 2 * ( a - 1 ) + 1 = a ^ 2 ;
    a ^ 2 - 2 * a * 1 + 1 ^ 2 + 2 * a - 2 * 1 + 1 = a ^ 2 ;
    a ^ 2 - 2 * a + 1 + 2 * a - 2 + 1 = a ^ 2 ;
    a ^ 2 + 1 - 2 + 1 = a ^ 2 ;
    a ^ 2 + 2 - 2 = a ^ 2 ;
    a ^ 2 = a ^ 2 ;
    Верно;

    в) (x+1)^2-4(x+1)+4=(x-1)^2;
    x ^ 2 + 2 * x + 1 - 4 * x - 4 + 4 = ( x - 1 ) ^ 2 ;
    x ^ 2 - 2 * x + 1 = ( x - 1 ) ^ 2 ;
    ( x - 1 ) ^ 2 = ( x - 1 ) ^ 2 ;
    Верно;

    г) (x-y)^2-2(x-y)(x-y)+(x-y)^2=4y^2 ;
    x ^ 2 - 2 * xy + y ^ 2 - 2 * x ^ 2 + 2 * y ^ 2 + x ^ 2 - 2 * x * y + y ^ 2 = 4 * y ^ 2 ;
    - 4 * xy + + 4 * y ^ 2 = 4 * y ^ 2 ;
    Неверно.
    0